The Family Cladoniaceae (Lecanorales) in the Galapagos Islands - Yánez, Alba; Ahti, Teuvo; Bungartz, Frank (Phytotaxa, 2013)
As part of an ongoing comprehensive inventory of the Galapagos lichen flora, all species in the Cladoniaceae from the archipelago have been revised using both historic and recent collections. A total of twenty-six species is reported here, one species of Cladia and twenty-five Cladonia species. One species, Cladonia bungartzii, is described as new to science; seven are records new to Ecuador and the Galapagos: Cladonia corymbosula, C. polyscypha, C. pulverulenta, C. pyxidata, C. aff. sphacelata, and C. strepsilis. Four species have previously been reported from Ecuador, but are new to Galapagos: C. cartilaginea, C. chlorophaea, C. dactylota, and C. grayi. Eight species previously reported cannot be confirmed here. Detailed descriptions are presented for all species. They include diagnostic characteristics to distinguish similar species. An identification key to all Galapagos Cladoniaceae is provided. A brief discussion highlights the importance of baseline inventories and uses the Galapagos Cladoniaceae as a case study to discuss important aspects of lichen biogeography in Galapagos.